In vitro and in vivo effect of peptides derived from 14-3-3 Paracoccidioides spp. Protein - Scorzoni, Liliana [UNESP]; E Silva, Ana Carolina Alves de Paula [UNESP]; de Oliveira, Haroldo Cesar [UNESP]; Dos Santos, Claudia Tavares [UNESP]; Singulani, Junya de Lacorte [UNESP]; Assato, Patricia Akemi [UNESP]; Marcos, Caroline Maria [UNESP]; Oliveira, Lariane Teodoro [UNESP]; Fregonezi, Nathália Ferreira [UNESP]; Rossi, Diego Conrado Pereira; da Silva, Leandro Buffoni Roque; Taborda, Carlos Pelleschi; et al. (MDPI, 2021)
Background: Paracoccidioidomycosis (PCM) is a chronic disease that causes sequelae and requires prolonged treatment; therefore, new therapeutic approaches are necessary. In view of this, three peptides from Paracoccidioides brasiliensis 14-3-3 protein were selected based on its immunogenicity and therapeutic potential. Methods: The in vitro antifungal activity and cytotoxicity of the 14-3-3 peptides were evaluated. The influence of the peptides in immunological and survival aspects was evaluated in vivo, using Galleria mellonella and the expression of antimicrobial peptide genes in Caenorhabditis elegans. Results: None of the peptides were toxic to HaCaT (skin keratinocyte), MRC-5 (lung fibroblast), and A549 (pneumocyte) cell lines, and only P1 exhibited antifungal activity against Paracoccidioides spp. The peptides could induce an immune response in G. mellonella. Moreover, the peptides caused a delay in the death of Paracoccidioides spp. infected larvae. Regarding C. elegans, the three peptides were able to increase the expression of the antimicrobial peptides. These peptides had essential effects on different aspects of Paracoccidioides spp. infection showing potential for a therapeutic vaccine. Future studies using mammalian methods are necessary to validate our findings.
Keywords: 14-3-3 protein; Caenorhabditis elegans; Galleria mellonella; Paracoccidioides spp; Paracoccidioidomycosis; Vaccine